2021
DOI: 10.3390/ma14040837
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Microporosity Formation of IN718 Alloy during Laser Cladding Based on Cellular Automaton

Abstract: Porosity is one of the most common defects in the laser cladding of Inconel 718 (IN718) alloy, which can reduce the strength and fatigue performance of the components. However, the dynamic formation of microporosity is challenging to observe through experiments directly. In order to explore the formation mechanism of porosities and dynamically reproduce the competitive growth between porosities and dendrite, a multi-scale numerical model was adopted, combined with a cellular automaton (CA) and finite element m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The dimensions of the thin-wall specimens were 40 mm (along the laser deposition direction) × 3 mm × 50 mm (along the laser scanning direction). The process parameters were determined according to the previous study [ 20 ] and the detailed parameters are listed in Table 2…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dimensions of the thin-wall specimens were 40 mm (along the laser deposition direction) × 3 mm × 50 mm (along the laser scanning direction). The process parameters were determined according to the previous study [ 20 ] and the detailed parameters are listed in Table 2…”
Section: Methodsmentioning
confidence: 99%
“…The dimensions of the thin-wall specimens were 40 mm (along the laser deposition direction) × 3 mm × 50 mm (along the laser scanning direction). The process parameters were determined according to the previous study [20] and the detailed parameters are listed in Table 2 Materials 2021, 14, x FOR PEER REVIEW 4 of 13 (CLSM, OLYMPUS, Tokyo, Japan) observed and measured the microstructure and chemical composition, respectively. The chemical composition of the phase in the molten was characterized by the energy spectrometer with SEM, and the acceleration voltage in EDS analysis is 20 kV.…”
Section: Experimental Parametersmentioning
confidence: 99%
“…Laser cladding is one of the promising methods for manufacturing and repairing different industrial components such as pump shafts and turbine blades [4][5][6][7]. IN718 nickelbase superalloy has high strength, satisfying toughness, and corrosion resistance below 650 • C [8,9]. Thus, laser cladding IN718 coating is able to contribute to the improvement of the service life of Cr5Mo substrate in a high-temperature corrosion environment.…”
Section: Introductionmentioning
confidence: 99%
“…Akbari et al 20 combined the CA model with the Kocks-Mecking (KM) and Laasraoui-Jonas models to establish a finite-element model, and the simulation results were in good agreement with the experimental results. Lv et al 21 combined CA and finite-element methods to simulate equiaxed and columnar dendrites with pores in IN718 alloy. Comparing the simulation results with the experimental data, it is found that the simulation results of the equiaxed crystal region are close to the experimental data, but there is a relative error in the columnar crystal region.…”
Section: Introductionmentioning
confidence: 99%